Triton X-100β-Cyclodextrin cloud point extraction for removal of phenol using different of sodium salts as inducing phase separation agent - Asman, Saliza; Abas, Nur Azlie (Asian Journal of Chemistry, 2018)
A simple and low-cost cloud point extraction (CPE) method was developed for the removal of phenol in water samples prior to its spectrophotometric detection. Two CPE methods; CPE-(TX/βCD)-NaOH and CPE-(TX/βCD)-Na2CO3 were developed based on Triton X-100/β-cyclodextrin (TX-100/β-CD) using electrolytes of sodium hydroxide (NaOH) and sodium carbonate (Na2CO3), respectively as inducing phase separation agents. The effects of parameters; electrolytes, surfactant, β-CD, and analyte concentrations, temperature, incubation time, and pH were evaluated in the context of extracting phenol from an aqueous media. Under optimized conditions, the CPE-(TX-βCD)-NaOH was selected to extract phenol from real water samples due to its superior performance vis-à-vis the CPE-(TX-βCD)-Na2CO3. The calibration curve was linear in the range of 1.0 mg L-1 to 3.0 mg L-1 of phenol, with a regression coefficient of 0.9855. The extraction efficiency in spiked and without spiked phenol in real water samples was in the range of 91.9 - 116.1 %. The results confirmed that the developed method can be applied satisfactorily to detect the presence of phenol in real water samples.